(untitled) (Perner’s Contacts, 2012)
Smart speed control of a car is the focus of the paper. There is introduced the possibility how to automatically control the car speed smoothly in the daily traffic. The technique uses nonlinear neural car model together with differential evolution search technique to determine continuously convenient throttle power so that the car speed is optimal with respect to defined cost function – the cost function can consider actual speed limits as well as speed smoothness.